Isorhamnetin ameliorates inflammatory responses and articular cartilage damage in the rats of monosodium iodoacetate-induced osteoarthritis. (4th July 2019) - Tsai, Sen-Wei; Lin, Chi-Chien; Lin, Shih-Chao; Wang, Shun-Ping; Yang, Deng-Ho
Abstract: Context: Osteoarthritis (OA) is a degenerative joint disease with damage to the articular cartilage. Active production of inflammatory cytokine/chemokine and matrix metalloproteinases may be found during the progression of OA. Isorhamnetin had the effects of anti-inflammatory, antioxidant, anti-ischemia, anti-atherosclerotic hepatoprotective and anticancer activities. Objective: Our study was focused on the effects of isorhamnetin treatment in OA. Materials and methods: We used monosodium iodoacetate (MIA)-induced OA rats to evaluate the effects of isorhamnetin related anti-inflammatory process. The rats in all groups were sacrificed on four weeks post-MIA injection. The measurements of knee joint swelling, histological analysis, serum inflammatory biomarkers and western blot were evaluated. Results: We found that isorhamnetin may reduce MIA-induced knee swelling by significantly reduction of articular cartilage damage.in rats. Suppression of pro-inflammatory cytokines production was found after isohamnetin treatment. Isorhamnetin inhibited the production of NO and PGE2, and the expression of iNOS and COX-2. The production of COMP, CTX-II and osteopontin (OPN) were also inhibited in MIA-induced OA rats. Discussion and conclusions: Isorhamnetin may modulate the inflammatory progression of OA in MIA-induced OA rats. The prevention of cartilage damage was found in OA after adequate isorhamnetin treatment. Isorhamnetin may serve as a potential agent for the management of OA.